Law and Social Dynamics of Society - Utama, Andrew Shandy (International Journal of Law and Public Policy (IJLAPP), 2021)
This research aims to explain the influence of law on the social dynamics of society. The method used in this research is normative legal research. One of the sciences that studies the social dynamics of society is the Sociology of Law. Every dynamic that occurs as a result of social change requires a legal response. Social dynamics is a general phenomenon that occurs throughout the ages in every society, changes that occur in accordance with the nature and nature of humans who always want to make changes. The occurrence of social dynamics is influenced by several factors, including law, technology, community structure, culture, an open system of social stratification, and advanced education. Community institutions are considered truly valid if their norms fully assist the implementation of social patterns. The system of social layers can occur by itself or is deliberately structured to pursue a common goal. Legal coercion in the implementation of social institutions that apply as regulations is not always used. Instead, the emphasis is on the coercion of society.